Fair, square & legal : safe hiring, managing & firing practices to keep you & your company out of court - Weiss, Donald H., 1936- (American Management Association, 1995)
Fair, Square & Legal is a concise, one-stop guide to what you as a manager should and shouldn't do if you want to stay clear of trouble. This revised edition has been thoroughly updated throughout, and provides new coverage of the Family and Medical Leave Act, the Civil Rights Act of 1991, and the Americans with Disabilities Act. Written by an experienced manager, the book translates complex legal issues and precedents into a set of easy-to-follow guidelines for managing people. It provides both an overview of safe managerial procedures and a quick look-up source for specific situations you may encounter. The book encompasses a broad range of potential problem areas. For each, author Donald H. Weiss supplies non-legalese definitions of key terms, practical guidelines for what to say and do, fictionalized stories that illustrate both problems and solutions, and actual case studies of precedent-setting court decisions.